2018
DOI: 10.4236/jep.2018.912079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Land Use Changes on Carbon Stock Dynamics in Major Land Use Sectors of Mizoram, Northeast India

Abstract: Land use change activities have greatly affected the total ecosystem carbon stock (TECS) and also contribute to global change through emission of greenhouse gases. The present study assessed the change in vegetation biomass carbon stock (VBCS) and soil organic carbon stock (SOCS) following conversion in major land use sectors (agriculture, agroforestry, forest and plantation) in Mizoram, Northeast India. SOCS was the highest in agroforestry (50.85 Mg C ha −1) and the lowest in agriculture (33.99 Mg C ha −1). V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 66 publications
2
7
0
Order By: Relevance
“…The single-story vegetation in plantations favor homogenous growth environment, in contrast to the natural forests and shifting cultivation fallows. The forests, agroforests, and shifting cultivation fallows, as expected, had higher tree density and basal area than the plantation forests occupied by monoculture trees (Singh et al, 2018a). Relatively lower organic inputs and higher soil disturbance in the latter could have caused lower SOC stock than the former land uses (Singh et al, 2018b).…”
Section: Discussion Tree Diversity In Different Land Usessupporting
confidence: 52%
See 3 more Smart Citations
“…The single-story vegetation in plantations favor homogenous growth environment, in contrast to the natural forests and shifting cultivation fallows. The forests, agroforests, and shifting cultivation fallows, as expected, had higher tree density and basal area than the plantation forests occupied by monoculture trees (Singh et al, 2018a). Relatively lower organic inputs and higher soil disturbance in the latter could have caused lower SOC stock than the former land uses (Singh et al, 2018b).…”
Section: Discussion Tree Diversity In Different Land Usessupporting
confidence: 52%
“…The confounding effects from other soil characteristics and management regimes may affect carbon stock too (Newaj et al, 2016). The rate of carbon sequestration in a habitat is influenced by several factors such as age of the stand/ maturity index, management, and woody species composition (Singh et al, 2018a). The elevation, slope, and aspect could also influence the carbon sequestration rate (Gogoi et al, 2020;Thong et al, 2020).…”
Section: Effect Of Land-use Change On Carbon Balancementioning
confidence: 99%
See 2 more Smart Citations
“…Soil C stock (Mg ha -1 ) in different land-use systems. LSD is shown at p < 0.05. cently,Singh et al (2018) reported the highest soil C stock in agroforestry land use (50.85 Mg C ha −1 ) and the lowest in agricultural cropland(33.99 Mg C ha −1 ) when compared with forest and plantations of Mizoram. OPP and HG at upper depth suggested that the surface soil is more active for sequestering C from the atmosphere after the land use change Haghdoost et al (2013).…”
mentioning
confidence: 96%